Building of Knowledge on Standardization of Forensic Expert Activities in Russia - E. V. Chesnokova (Теория и практика судебной экспертизы)
Basing on the analysis of historical events and achievements in forensic science, the author proposes a periodization for the building of knowledge on the standardization in forensic activities in Russia. The author also shows that implementation of the standardization in forensic activities and the development of appropriate practical procedures were critically influenced by the isolation of the Soviet system and subsequent stable scientific and practical international contacts; improvement of the regulatory framework of forensic activities, standardization, and technical regulation in the Russian Federation; continuity of the domestic Soviet science and practice in forensic expertise. For a holistic understanding of the functioning of all the tools and mechanisms of standardization at different stages of the evolution of forensic expertise, the author proposes to develop a model of a subtheory of standartization for forensic expert activity and implement it.